2020
DOI: 10.11005/jbm.2020.27.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Is Full-Length Intramedullary Nail Necessary for Atypical Subtrochanteric Femoral Fracture Associated with Bisphosphonate?

Abstract: Background: American Society for Bone and Mineral Research recommend the use of intramedullary reconstruction of full length-nail for atypical subtrochanteric femoral fracture (ASFF). However, there is no study on the incidence of the ipsilateral femoral fracture after index operation of ASFF, and full-length nail has disadvantage as iatrogenic fracture and leg length discrepancy (LLD). The aim of this study was to investigate the incidence of ipsilateral secondary fracture after using partial-length nail, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The appropriate length of the intramedullary nail for atypical subtrochanteric femoral fracture fixation is controversial. Kim et al [ 9 ] compared the clinical outcomes of partial- and full-length nails used for atypical subtrochanteric femoral fractures and concluded that full-length nails are not usually required. According to their report, no ipsilateral secondary atypical femoral fractures were found during the follow-up period; however, the mean follow-up period was a short 1.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate length of the intramedullary nail for atypical subtrochanteric femoral fracture fixation is controversial. Kim et al [ 9 ] compared the clinical outcomes of partial- and full-length nails used for atypical subtrochanteric femoral fractures and concluded that full-length nails are not usually required. According to their report, no ipsilateral secondary atypical femoral fractures were found during the follow-up period; however, the mean follow-up period was a short 1.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] Regarding the type of nail, a full-length intramedullary nail is preferred [ 31 ]; however, a partial-length intramedullary nail has also shown similar outcomes as full-length nail. [ 32 ] In this case, we chose to treat our patient conservatively due to her severe lateral femoral bowing. More specifically, insertion of a relatively straight intramedullary nail into a curved bone would be technically challenging and may not effectuate the intended effect.…”
Section: Discussionmentioning
confidence: 99%
“…Made up mainly of metal alloy, it has been successfully applied in orthopedics clinics. 3 Studies have shown that this system has the biomechanical characteristics of central fixation and has become the first choice in the clinical treatment of patients with intertrochanteric fractures. 4 The common clinical intramedullary nail fixation devices include proximal femoral combined tension interlocking intramedullary nail (InterTan) and Asian proximal femoral anti rotation intramedullary nail (PFNA-II).…”
Section: Introductionmentioning
confidence: 99%
“…Made up mainly of metal alloy, it has been successfully applied in orthopedics clinics. 3 Studies have shown that this system has the biomechanical characteristics of central fixation and has become the first choice in the clinical treatment of patients with intertrochanteric fractures. 4 …”
Section: Introductionmentioning
confidence: 99%